Application of satellite images analysis to assess the variability of the surface thermal heat island distribution in urban areas - Fudała Janina; Nádudvari Ádám; Bronder Joachim; Fudała Marta (E3S Web of Conferences, 2018)
One of the elements of the urban plans for adapting to climate change is to identify the range the urban heat island (UHI). To a relatively rare ground station network air temperature, one of the possible methods to identify this phenomenon in cities is the analysis of satellite images, and in particular the thermal images surface cities in conjunction with the land-use structure. In the publication is presented the application of indirect methods of determining surface characteristics of heat island in the cities of Upper Silesia Agglomeration on the basis of the analysis of the thermal images from the satellite Landsat for the period 1986-2016. It presents ways to interpret these images depending on the needs of determination the areas sensitive to the impact of the (UHI) and define the areas where adaptation actions to the climate change should be undertaken.